(untitled) (Revista Contexto & Educação, 2023)
The aim of this article is to understand the situation of the recycling professionals, during the COVID-19 pandemic, in relation to social inequality and the potential of popular as a contributor to facing their problems. Through bibliographic research, news, official data, decrees, laws and bibliographies on the subject were evaluated. In the analysis, it was possible to verify that the ways of facing adversity were and are diverse during the pandemic. For recycling professionals, it can be observed that popular education, as an educational practice, for the constitution of an organization process for the purpose of resistance and struggle for the affirmation of the dignity of life and work.